Kontribusi Gaya Kepemimpinan, Budaya Sekolah dan Motivasi pada Peningkatan Kinerja Guru (Studi Kasus Madrasah Aliyah Negeri 1 Pidie – Aceh) - Mawarriyanti, Mawarriyanti; Bariah, Chairul (peusangan, 2024)
The study is intended to review the contribution of factors to improving teacher performance based on leadership style, organizational culture and teacher work motivation. The study was conducted through a survey of 50 teachers of Madrasah Aliyah Negeri (MAN) 1 Pidie, with associative-quantitative methods and problem analysis with path analysis models. Based on the results of the study, it was found that there was a significant contribution of leadership style factors, school culture and teacher work motivation to strengthening performance of 50.3 percent, 23.8 percent and 30.3 percent respectively. Together, the three factors play a role in improving performance by 52.7%. So to improve the quality of teacher performance, it is expected that schools will improve their leadership, maintain school culture and motivate their teachers to work.